Pain Due to Multiple Sclerosis: Analysis of the Prevalence and Economic Burden in Canada - Charles Piwko; Olivier B Desjardins; Basil G Bereza; Marcio Machado; Barbara Jaszewski; Mark S Freedman; Thomas R Einarson; Michael Iskedjian (Pain Research and Management)
BACKGROUND: Multiple sclerosis (MS) is a neurological disease affecting approximately 50,000 Canadians. Although studies have described overall MS costs, none have focused specifically on MS-related pain.